In Search of Lost National Epic: Poem Kastītis ir Juraite by Auszra poet Andrius Vištelis - Kristinaitytė, Ieva (Literatūra, 2024)
The article discusses the manuscript poem Kastītis ir Juraite (1889) by Andrius Vištelis and the vision of an imagined utopian Lithuanian culture emerging in the poem. Vištelis was a then-known poet of the 19th-century Lithuanian national movement who, in the current historiography, is perceived as a marginal writer. The poem has not been analysed until now, although it is one of the earliest texts in Lithuanian about the myth of Jūratė and Kastytis. The poem can be considered as an attempt to create the missing Lithuanian national epic for the emerging modern Lithuanian national community. The cultural tensions and negotiations that appear in the poem are reviewed. The images appearing in the poem that was destined to unite the community are also analysed.The first part of the article discusses the paradigm of poetic and linguistic reconstruction and its significance for the creative program of one of the initiators of Auszra, thus including Vištelis in the significant field of the romanticism, which was manifested in the Polish-Lithuanian Commonwealth, whereas the second part analyses the idea of a new egalitarian society proclaimed in the poem Kastītis ir Juraite in the 19th century through the context of utopias. In the analysed poem, a new religion emerges, which was supposed to combine pagan and Christian ‘traditions’. The circulation of Hugues Felicité Robert Lamennais philosophy on the work of Vištelis is discussed, the circumstances of the poem’s creation are specified, and the possible narrative of the poem is reconstructed from the drafts, thereby supplementing the discourse of the first national Lithuanian paper Auszra.
Keywords: Kastytis and Jūratė; cultural negotiations; cultural vision; paganism; utopia